The international legal frameworks to combat cybercrime in the era of artificial intelligence - Abdallah, Mekhaneg; Abdallah, Amar Youcef (International journal of economic perspectives, 2025)
In the era of Artificial Intelligence, cybercrime has emerged as a new phenomenon, and has spread at a speed that exceeds the imaginations. It has crystallized as a result of the unprecedented scientific leap that has made a difference in the field of Information and Communication Technology, and has reduced the distances between people. This crime is still a source of widespread threats that damage personal data destabilize societies. This new crime has various forms, and its consequences are difficult to accurately determine, which requires the international legal system to be adapted to these complexities. Face to the repeated electronic piracy attacks, it has become necessary for the International Community, more than ever, to rely on international legal frameworks in light of the comprehensive approach, through International Conventions on combating transnational crimes. This involves an attempt to reduce the scale and repercussions of these crimes and ensure the security of cyberspace, while respecting the standards of international law. In regard of the current challenges, combating cybercrime requires all international actors to adopt effective strategies that take into account the respect for the principle of sovereignty, the protection of the rights and freedoms of individuals, and at the same time preserving the National Security of States.